2015
DOI: 10.1038/srep18435
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biotechnological Potential Analysis of a New Exopolysaccharide from the Arctic Marine Bacterium Polaribacter sp. SM1127

Abstract: Although many kinds of exopolysaccharides (EPSs) from microorganisms have been used in industry, the exploration and utilization of EPSs from polar microorganisms is still rather rare. In this study, a flavobacterial strain, SM1127, from the Arctic brown alga Laminaria, was screened for its high EPS production (2.11 g/l) and was identified as belonging to the genus Polaribacter. The EPS secreted by strain SM1127 has a molecular mass of 220 kDa, and it mainly comprises N-acetyl glucosamine, mannose and glucuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 53 publications
3
64
0
Order By: Relevance
“…For example, the study of Sun et al found that the hygroscopicity of EPS produced by arctic Marine bacteria was higher than chitosan, but lower than hyaluronic acid. Besides, its moisture retention ability was higher than that of chitosan and alginate [31]. However, few studies can clearly explain these properties of EPS.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the study of Sun et al found that the hygroscopicity of EPS produced by arctic Marine bacteria was higher than chitosan, but lower than hyaluronic acid. Besides, its moisture retention ability was higher than that of chitosan and alginate [31]. However, few studies can clearly explain these properties of EPS.…”
Section: Discussionmentioning
confidence: 92%
“…SM1127; it has been reported that the DPPH • , • OH, O 2 -• scavenging activities of the EPS at a concentration of 10 mg/mL were 55.4 ± 3%, 52.1 ± 2.1% and 28.2 ± 3%, respectively, which is similarly higher than those of hyaluronic acid. 40 Free radicals can greatly affect human health and cause various diseases such as ageing and inflammation in the body 41 ; for this reason, researchers are always looking for biopolymers that are antioxidant and can reduce the harm caused by free radicals in the human body. Sun et al suggested that the ability of an EPS in scavenging of free radicals may be due to the presence of functional groups such as -O-, C=O and -OH in its structure.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Sun et al suggested that the ability of an EPS in scavenging of free radicals may be due to the presence of functional groups such as -O-, C=O and -OH in its structure. 40 It is well accepted that the mentioned functional groups can donate electron or hydrogen ions to reduce the free radicals and can bind directly with the free radicals to form stable radicals. 40,42 As shown previously in the spectrum obtained from FT-IR, the existence of the mentioned functional groups in the EPSs structure was confirmed.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of antioxidant EPS from polar bacteria is less reported, but some researchers have detected attractive structures, such as from the Arctic marine bacterium Polaribacter sp. SM1127 [259]. SM1127 EPS has a molecular weight of 220 kDa and is comprised of N-acetylglucosamine (GlcNAc), Man, GlcA, Fuc, Glc, and Rha residues, which are connected in a complex way.…”
Section: Exopolysaccharides From Bacteriamentioning
confidence: 99%